Tatalaksana Medikamentosa pada Low Back Pain Kronis - M. Muhlis Rizki; Fitria Saftarina (Majority, 2020)
Low back pain (LBP) is a leading cause of disability throughout the world. The prevalence of low back pain is reported to be as high as 84%, with 12% of the population being disabled by low back pain. The prevalence in Indonesia is 24,7%, most of them are related with occupation that involves with the strength of spine, resulting in overload and trigger the accelerated degenerative articular. Based on the duration of pain, LBP is divided into acute, subacute, and chronic. Low back pain that persists for more than 12 weeks is defined as chronic LBP. Chronic LBP requires multimodal therapy, but seems to follow the main principle, such as to reduce the pain, to prevent muscle stiffness, and to enhance patients’ quality of life. The most common drugs used to treat pain in chronic LBP are NSAID, gabapentinoid, and muscle relaxant. NSAID, as the first modality to treat chronic LBP, works by inhibiting prostaglandin through the inhibition of both COX 1 and 2 (non-selective) or directly of COX 2 (selective). The use of NSAID is limited in patients with gastrointestinal and cardiovascular symptoms. Gabapentinoid is an anti-convulsant drug which involves in neurotransmitter modulation in afferent neuron presynaptic receptors, but this drug requires titration and it should be taken for considerations. Lastly, muscle relaxant is categorized into two different mechanisms, which directly works in spinal cords and skeletal muscles (antispastic) and in central nervous system conduction (antispasmodic) to prevent muscle spasms, but still considering about the risk of drug abuse. By taking all side effects of all therapy modalities into consideration, NSAID is chosen as first-line therapy to treat chronic LBP.